Angiodrastic Chemokines in Colorectal Cancer: Clinicopathological Correlations - George Emmanouil; George Ayiomamitis; Adamantia Zizi-Sermpetzoglou; Maria Tzardi; Andrew Moursellas; Argyro Voumvouraki; Elias Kouroumalis (Analytical Cellular Pathology)
Aim. To study the expression of angiodrastic chemokines in colorectal tumors and correlate findings with clinicopathological parameters and survival. Methods. The proangiogenic factor VEGF, the angiogenic chemokines CXCL8 and CXCL6, and the angiostatic chemokine CXCL4 were measured by ELISA in tumor and normal tissue of 35 stage II and III patients and correlated with the histopathology markers Ki67, p53, p21, bcl2, EGFR, and MLH1 and 5-year survival. The Wilcoxon and chi-square tests were used for statistical comparisons. Results. There was a significant increase of CXCL6 (p=0.005) and VEGF (p=0.003) in cancerous tissue compared to normal. Patients with lower levels of CXCL8 and CXCL4 lived significantly longer. Patients with loss of EGFR expression had higher levels of CXCL8 while p21 loss was associated with higher levels of CXCL6. Chemokine levels were not correlated with TNM or Dukes classification. Strong expression of p53 was accompanied by decreased survival. Conclusions. (1) The angiogenic factors CXCL6 and VEGF are increased in colorectal cancer tissue with no association with the clinical stage of the disease or survival. (2) However, increased levels of tissue CXCL8 and CXCL4 are associated with poor survival. (3) Strong expression of p53 is found in patients with poor survival.